Estudio teórico comparativo de desempeño termodinámico y de emisiones de un motor de pistones opuestos diésel de dos tiempos respecto a un motor de pistones en línea diésel de cuatro tiempos (2021)
The use of less polluting and efficient engines has become a policy to improve the quality of life of the population; The research project presented aims to carry out a comparative theoretical study of thermodynamic performance and emissions of the two stroke opposed piston engine with respect to a fourstroke Diesel engine, both with the same displaced volume, compression ratio and type of fuel. ; The applied methodology compares a four-- stroke engine and a Dual engine, based on their thermodynamic cycles, efficiencies and emissions; Th e results indicate that the efficiency of the Diesel nickname was 49.46%, while that of the Dual was 61.04%; Regarding the carbon dioxide emitted, the MP10 was 60.57 and the Jumbo 20 indicated thermal efficiency, p 7A was 73.88. The dual engine has a higher roviding higher polluting emissions (CO stroke diesel engine